Heart‐lung transplantation: A viable option for connective tissue diseases. Issue 2 (9th January 2020) - Stern, Lily K.; Selby, Van N.; Kolaitis, Nicholas A.; Boin, Francesco; Aras, Mandar; Klein, Liviu; De Marco, Teresa
Abstract: Background: While lung transplantation (LTx) has been effective for connective tissue disease (CTD) patients with pulmonary involvement, outcomes for heart‐lung transplantation (HLTx) are less defined. The aim of this study is to evaluate HLTx in CTD patients utilizing the UNOS database. Methods: HLTx patients with CTD (HLTx‐CTD) were compared to both LTx patients with CTD (LTx‐CTD) and HLTx patients with all other indications (HLTx‐OI) from 1999 to 2018. Primary outcome was 1‐ and 5‐year graft survival. Secondary outcomes included freedom from first‐year rejection and outcomes prior to transplant discharge. Results: 1143/29 323 adults received first‐time HLTx or LTx for CTD. Seventeen were HLTx‐CTD (3.3% of total HLTx) and 1126 were LTx‐CTD (3.9% of total LTx). There were 492 HLTx‐OI. Transplant hemodynamic values including cardiac output, pulmonary capillary wedge pressure, and calculated pulmonary vascular resistance were significantly worse for HLTx‐CTD vs LTx‐CTD (4.2 vs 5.4 L/min, P = .005; 14 vs 10 mm Hg, P = .009; 439 vs 267 dynes, P = .007, respectively). Cardiac status 1 was more common for HLTx‐CTD vs HLTx‐OI (94% vs 56%, P < .001). HLTx‐CTD 1 and 5‐year graft survival was similar compared to LTx‐CTD and HLTx‐OI. Conclusion: HLTx‐CTD is a valid option for carefully selected patients with CTD cardiac and pulmonary involvement with similar morbidity and mortality compared to LTx‐CTD and HLTx‐OI.